Association of recurrent pregnancy loss and anticardiolipin antibodies: prevalence and prognosis of subsequent pregnancy in women with recurrent pregnancy loss - Verabelly, Malathi; Seedipally, Swapnarani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Anticardiolipin antibodies (ACA) are found with increased prevalence in women with unexplained recurrent pregnancy loss but their impact on future pregnancy is not clearly known. Therefore, present study objective was to compare the prevalence of ACA in patients with recurrent pregnancy loss and normal healthy pregnant women. Methods: This prospective observational study from 100 pregnant women attending the outpatient department of Obstetrics and Gynaecology were studied. Study included 50 pregnant women with a history of three or more consecutive unexplained pregnancy loss as a study group and 50 pregnant women with two or more live children with no history of any previous pregnancy loss as a control group. Exclusion criteria included cases with any uterine anomaly, uterine structural abnormalities, induced abortions, infections, systemic disease, Rh-ve pregnancy, coagulation disorders and personal or family history of thrombosis. Results: Overall, 9 patients tested positive for ACA, of which one (2%) patient was from the control group and remaining 8 (16%) were from study group. Overall, 42 (84%) patients had negative test for ACA in the study group and 49 (98%) patients in the control group. The live birth rate among study group was only 34 (68%) whereas all 50 (100%) pregnant women in the control group. Conclusions: The findings described here in demonstrate that, ACA -positive patients are also the primary predictor of adverse pregnancy outcome and obstetric complications. Therefore, the role of early detection of ACA in all pregnant women is very important to prevent foetal outcomes and obstetric complications.